2013
DOI: 10.1524/ract.2013.2016
|View full text |Cite
|
Sign up to set email alerts
|

Development and demonstration of a new SANEX Partitioning Process for selective actinide(III)/lanthanide(III) separation using a mixture of CyMe4BTBP and TODGA

Abstract: SANEX / Minor actinides / Americium / Curium / Partitioning / TODGA / CyMe 4 BTBP Summary. Within the framework of the European collaborative project ACSEPT, a new SANEX partitioning process was developed at Forschungszentrum Jülich for the separation of the trivalent minor actinides americium, curium and californium from lanthanide fission products in spent nuclear fuels. The development is based on batch solvent extraction studies, singlecentrifugal contactor tests and on flow-sheet design by computer code c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 30 publications
(45 reference statements)
2
50
0
Order By: Relevance
“…However, this is not the case for Eu(III), which is why selectivity decreases with decreasing t-Bu-CyMe 4 -BTBP concentration. This effect is also reported for the CyMe 4 -BTBP + DMDOHEMA [13] and CyMe 4 -BTBP + TODGA [18] systems.…”
Section: Acid Concentration Dependencesupporting
confidence: 77%
See 2 more Smart Citations
“…However, this is not the case for Eu(III), which is why selectivity decreases with decreasing t-Bu-CyMe 4 -BTBP concentration. This effect is also reported for the CyMe 4 -BTBP + DMDOHEMA [13] and CyMe 4 -BTBP + TODGA [18] systems.…”
Section: Acid Concentration Dependencesupporting
confidence: 77%
“…Would t-Bu-CyMe 4 -BTBP be applicable in a process, similar to the ones performed using CyMe 4 -BTBP? [17,18] Probably yes. Its slower kinetics could be compensated by increasing its concentration since extraction rate in similar systems increases first order with the extracting agent concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Modolo et al recently proposed that 0.25 mol/L DMDOHEMA can be substituted with 0.005 mol/L TODGA. [17] This system shows comparably good extraction properties and kinetic behavior compared to DMDOHEMA, and the performance of the system was demonstrated in a spiked test. The experiments conducted by both groups used a DIAMEX product solution containing actinides and lanthanides as a SANEX feed solution.…”
Section: Introductionmentioning
confidence: 87%
“…Recent studies have shown that poly-aromatic nitrogen compounds, N-PAHs, acting as tetradentate chelating ligands to the metal ions in the extraction, have the ability to sufficiently separate An(III) from Ln(III). [7][8][9][10] One of these N-PAHs, 6,6'-bis (5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzol [1,2,4]triazin-3-yl) [2,2]bipyridine, CyMe4-BTBP (Figure 1), has promising process potential, [11][12][13][14][15][16] as it has proven to be resistant towards acidic environments [17][18][19] and strong radiation from radioactive decomposition 13,20 Qualitative reasoning concerning the Lewis basicity of the extractant and the somewhat softer character of the actinoid(III) ions compared to the lanthanoid(III) ones has been used to explain the An(III)/Ln(III) separation capacity of N-PAH ligands. 32,33 An(III)/Ln(III) separation by CyMe4-BTBP has also been observed to vary with the solvent used.…”
Section: Introductionmentioning
confidence: 99%